SITUS DORO BENTE PADA BEKAS KERUCUT SINDER PETI-TABEH: KORIDOR BARU PENELUSURAN JEJAK KERAJAAN YANG HILANG - I Putu Yuda Haribuana (Forum Arkeologi, 2017)
Research in the area of Tambora has been done in several stages, but still not enough to identify the center of the buried kingdoms. The purpose of this research is to obtain the latest data outside the Tambora Site, but still within the region of Mount Tambora. Doro Bente Site is located in Sori Tatanga Village, Pekat District, Dompu Regency, West Nusa Tenggara. Data collection was done through survey and excavation, then analyzed using special, contextual, and comparative methods. The result of this research shows that there is a traditional stronghold and also a variety of artifacts found at this site. This suggests that the remains of Doro Tabeh cinder cone was once used as a refuge and temporary settlement.